Desarrollo de un sistema para el análisis de corrección del factor de potencia en una red trifásica con cargas desequilibradas. - Azogue Pilicita, Henry Danilo (2022)
One of the problems that affect the industries is the low power factor, due to the excess inductive load and the difficulty of relating sinusoidal and phasor graphs of electrical variables in the power factor correction process, for this reason the development of a system that allows the interaction between electrical parameters (voltage, current, power) to visualize and measure in real time the behavior of these variables in a three-phase network, through the design of a module that through experimental practices proposes to observe waves sinusoidal and phasor diagrams of the entire process described above. With the use of resistive, capacitive and inductive loads, it will be possible to analyze the behavior of the three-phase network, through an energy meter "SENTRON PAC 3220" necessary for the study of this case, and with the creation of a didactic graph in the LabVIEW software. It will allow the user to generate a signal processing to compare calculated data with real data obtained in the process of this practice, as well as focus on the phase shift of the voltage with respect to the current, visualize phasor diagrams and sinusoidal waves. In addition, through external calculations it was possible to design a bank of capacitors that will be able to compensate the missing reactive energy to achieve a power factor correction, which is the objective of this system. Finally, a didactic system is obtained that allows to observe diagrams of the power factor correction process with the interaction of all the loads that are used in this module.